Preliminary Observation on Control of Slumping through Mangrove Afforestation at Nayachara, West Bengal (india) - a Case Study - Choudhuri, P. K. Roy (Indian Forester, 1994)
This paper deals with the prospect of raising mangrove plantation at Nayachara in the Midnapore District far away from the mangrove habitat. The plantation were initiated during the year 1990 and covered foreshore areas of Nayachara along the river Hooghly. Sonneratia apetala, with Avicennia Spp. Should be the principal species with minimal percentage of Bruguiera gymnorhiza (L) Lam and Rhizophora Spp. Tansplanting of longer and stouter nursery raised mangrove seedling in polypack in the interspaces of laterite boulders over geo-jute covering should ensure better performance in vulnerable areas. Such attempts have never been made earlier and there is very little information about artificial regeneration of mangrove species in these areas.